Prediction of Wheat Storage Process Under Climate Change: A Case Study of Northwestern Regions of Tunisia (American Journal of Agricultural Science, Engineering, and Technology, 2023)
In this work, a simulation of the climate change impact on the wheat grain storage process in Northwestern regions of Tunisia was investigated based on grain aeration systems. This simulation was conducted by implementing the software package called Zephyrus for a period from 2041 to 2070 during storage season from the 01st of July to the 30th of November. The model estimates grain moisture content, grain temperature, and dry matter loss. The results showed a significant potential of the Zypherus strategy to maintain the grain moisture content around 12.2± 0.2% w.b. and to reduce grain temperatures from 35°C to 24 ± 1.5°C inside the silo. Consequently, under these values, the wheat storage process is considered safe and preserves wheat quality during the simulated storage period. Moreover, the wheat dry loss matter was about 0.8% during the whole storage period for each simulated year (approximately 0.15% per month).